Undergraduate Public Health Education: Alternative Choices within the BSPH Degree - Perrin, Karen; Merrell, Laura (Frontiers in Public Health, 2014)
The University of South Florida’s College of Public Health, has been in existence since 1984. After many years of only offering a public health minor, a Bachelors of Science in Public Health was offered. This article explores the creation, development, scheduling, and lessons learned of this degree.